2020
DOI: 10.1016/j.celrep.2020.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Wss1 Promotes Replication Stress Tolerance by Degrading Histones

Abstract: Highlights d Wss1 promotes replication stress tolerance d Wss1 catalytic activity is essential for replication stress tolerance d Histone accumulation is toxic to Wss1 mutant cells during replication stress d Wss1 targets histones bound to single-stranded DNA during replication stress

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Validation of this hypothetical order of steps in proteolysis of DHC by the proteasome and Spartan requires more research. However, a recent study proved that Wss1 is actively involved in histone proteolysis in a NCP during replication stress (Maddi et al, 2020). Although this study showed that Wss1 removes histones non-covalently bound to DNA, it is very likely that this protease can also remove histones covalently cross-linked to DNA.…”
Section: Metalloprotease-based Proteolysis Of Histones Cross-linked Tmentioning
confidence: 77%
“…Validation of this hypothetical order of steps in proteolysis of DHC by the proteasome and Spartan requires more research. However, a recent study proved that Wss1 is actively involved in histone proteolysis in a NCP during replication stress (Maddi et al, 2020). Although this study showed that Wss1 removes histones non-covalently bound to DNA, it is very likely that this protease can also remove histones covalently cross-linked to DNA.…”
Section: Metalloprotease-based Proteolysis Of Histones Cross-linked Tmentioning
confidence: 77%
“…Even through non-covalent interaction, certain proteins such as yeast Fob1 or E. coli Tus can form effective DPC-like stable, high-affinity complexes with DNA that block replication fork movement [ 55 ]. Recently, histones in such non-covalent DPCs were shown to be substrates for Wss1 [ 56 ]. We postulate that Top1 mutants Y727F and Y740STOP, if forming replication barriers through high-affinity interaction with G4 DNA, could be SUMOylated and targeted by Wss1-dependent proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…This would explain the massive increase of unrepaired DSBs in the corresponding teb wss1A double mutant. Thus, in WT plants, WSS1A is able to suppress aberrant DSB formation by directly removing the replication-stalling obstacle or by protecting the stalled replication forks (Stingele et al, 2014;Enderle et al, 2019a;Maddi et al, 2020). We assume that the DSB-preventing function during replication is a conserved feature of WSS1A homologs in general.…”
Section: Wss1a Suppresses Formation Of Persisting Dsbmentioning
confidence: 93%
“…For WSS1A and RTR homologs, essential functions in maintaining replication fork stability were demonstrated in yeast and mammals. ScWss1 is able to degrade histones, which assemble at long single-stranded DNA straps of stalled replication forks, and thus the replication fork can be restored (Maddi et al, 2020). In humans, both RMI1 and the RECQ4A homolog BLM have been shown to interact with longer single-stranded DNA stretches coated by RPA.…”
Section: Wss1a Is Required For Replicative Dna Repairmentioning
confidence: 99%